Dogs' tales : representations of ancient Cynicism in French Renaissance texts - Roberts, Hugh (Hugh Gerald Arthur), 1977- (Faux titre, 2006)
Sleeping rough, having sex in public and insulting the most powerful men in the world earned the ancient Cynic or 'dog' philosophers fame and infamy in antiquity and beyond. This book reveals that French Renaissance texts feature a rich and varied set of responses to the Dogs, including especially Diogenes of Sinope (4th century B.C.), whose life was a subversive performance combining wisdom and wisecracks. Cynicism is a special case in the renewal of interest in ancient philosophy at this time, owing to its transmission through jokes and anecdotes. The Cynics' curious combination of seduction.